1985
DOI: 10.1161/01.res.56.4.586
|View full text |Cite
|
Sign up to set email alerts
|

Optimal arterial resistance for the maximal stroke work studied in isolated canine left ventricle.

Abstract: In a previous analysis of ventricular arterial interaction (Sunagawa et al., 1983), we represented the left ventricle as an elastic chamber which periodically increases its volume elastance to a value equal to the slope of the linear end-systolic pressure-volume relationship. Similarly, the arterial load property was represented by an effective elastance which is the slope of the arterial end-systolic pressure-stroke volume relationship. Since the maximal transfer of potential energy from one elastic chamber t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
289
1
7

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(303 citation statements)
references
References 17 publications
6
289
1
7
Order By: Relevance
“…53 The ability of E a , however, to represent the pulsatile component of arterial load has been questioned, 54 because it can be approximated by the ratio between total peripheral resistance (R) and heart cycle length (T). 52 If this was true, E a should have no relationship with the pulsatile component of the arterial load. Mathematical models 55 and human studies 56 have however demonstrated that arterial stiffness and pulsatile components of arterial load, although with a significantly Ventricular-vascular coupling in hypertension Saba et al 777 lesser extent than total peripheral resistance, play a role in determining the effective arterial elastance.…”
Section: 41mentioning
confidence: 99%
“…53 The ability of E a , however, to represent the pulsatile component of arterial load has been questioned, 54 because it can be approximated by the ratio between total peripheral resistance (R) and heart cycle length (T). 52 If this was true, E a should have no relationship with the pulsatile component of the arterial load. Mathematical models 55 and human studies 56 have however demonstrated that arterial stiffness and pulsatile components of arterial load, although with a significantly Ventricular-vascular coupling in hypertension Saba et al 777 lesser extent than total peripheral resistance, play a role in determining the effective arterial elastance.…”
Section: 41mentioning
confidence: 99%
“…E a was derived as the ratio of P es to SV. 19 We also calculated effective ejection fraction (EF e ) as the ratio of SV to stressed end-diastolic volume [end-diastolic volume (V ed )ϪV 0 ] as a measure of loading conditions. According to the framework of ventriculararterial coupling, EF e approximates the ratio of E es to E es ϩE a (Appendix).…”
Section: Definition Of Other Variablesmentioning
confidence: 99%
“…A more powerful and largely load‐independent measure of contractile function is LV end‐systolic elastance (E es ), which can be defined as the stiffness of the left ventricle at the end of the systole. The arterial system can also be assessed in elastance terms; hence, ventricular‐arterial coupling (VAC) can be expressed by the comparison of ventricular and arterial elastances (E a ) 12, 13, 14, 15. Experimental models showed that LV EW is maximal when the VAC (E es /E a ) ratio is 1,12 whereas the mechanical efficiency is maximal when the ratio is 2 13, 14.…”
Section: Introductionmentioning
confidence: 99%